STRUCTURAL DESIGN AND PERFORMANCE EVALUATION OF AN OFFICE BUILDING IN JAKARTA USING A DILATATION AND NON-DILATATION SYSTEM - Khairunnisa, Khairani
This final project document contains the design of the upper structure of an office building that has a height difference, featuring 14 floors of office towers and 6 floors of parking areas located in Jakarta. The design was conducted for both dilated and non-dilated structures using response spectrum analysis, which was then used to determine the performance of the structure through pushover analysis. The chosen structural system to carry lateral loads is a dual system, combining a special moment-resisting frame with shear walls, especially to anticipate the dominant torsion shape. The design rules for earthquake-resistant structures refer to SNI 1726:2019 and are supported by the requirements for designing reinforced concrete structures per SNI 2847:2019. The design of structural elements is based on the forces in the envelope results of the response spectrum analysis for each structure. A two-stage analysis was also conducted to determine the dimensions of the basement structural elements to meet the requirements of SNI 1726:2019. After designing the structural elements, an evaluation of the structural performance was conducted by referring to ATC-40 with plastic hinge modeling in accordance with ASCE 41-17. In general, it was found that structural dilation resulted in a reduction of irregularities in the building, thereby reducing the consequences that had to be applied in the design, which tended to make the structure more efficient. These results may vary with different geometric configurations, plans, and system structures.